Results of Research on the Physical and Mechanical Properties of Potato Culture - Payziev G. K; Abduxoliqov A. X (American Journal of Botany and Bioengineering, 2025)
The article presents research on the study of the physical and mechanical properties of potato stem and tubers, such as the tensile strength of the stem and stolon, the friction coefficient, which allows for the correct selection and justification of the installation location, the shape, and the parameters of the stem remover working element in the potato harvester.